The relationship between performance appraisal interval and employees’ proactive working behavior – analysis based on time-gain effect and time-loss effect - Yang, Jun; Ma, Jun; Li, Liping (Frontiers in Psychology, 2023)
Performance appraisal is the most widely motivation means for employees' initiative and work improvement. As a large number of organizations are moving from traditional annual performance appraisal to more frequent appraisals, there is little research to compare the motivational effect of different performance appraisal intervals. Therefore, we explore the relationship between performance appraisal interval (PAI) and positive work behavior (PWB) as well as how to improve the relationship between them. Drawing from the psychological momentum (PM) theory, we constructed a model of the dual effect (the time-gain effect and time-loss effect) of PAI on PWB as well as their boundary conditions. A cross-level analysis of 622 employees in 57 teams indicated that: (1) PAI exerted a positive but marginal decreasing effect on delay of gratification (DG), and then increase PWB indirectly (i.e., the time-gain effect). ( 2) PAI exerted a positive and marginal increasing effect on perceived uncertainty (PU), and then decrease PWB indirectly (i.e., the time-loss effect). ( 3) According to the additive principle of the benefit and cost proposed by Hanns et al ( 2016), the addition of the time-gain effect and time-loss effect leads to an inverted U-shape effect of PAI on PWB. (4) Supervisor developmental feedback (SDF) moderated the inverted U-shape effect of PAI on PWB. This research enriches the application of PM theory in performance appraisal research, advances employee proactivity research from a perspective of organizations' time mechanisms, and also provides a theoretical basis for leaders to adopt developmental feedback as an optimization strategy.